EXPERIMENTAL STUDY OF THE SURFACE ACTIVITY AND MICE PROPERTIES OF SAPONINS. (Universal International Scientific Journal, 2026)
In this work, the surface activity, micelle formation ability and colloidal-chemical properties of saponins of plant origin in aqueous solutions were studied using complex experimental methods. Surface tension was measured by the Du Nuy ring method, electrical conductivity by conductometry, and optical density by UV–Vis spectrophotometry. The critical micellization concentration (CMC), maximum adsorption (????°????????????), surface pressure (π), thermodynamic parameters calculated based on the Gibbs equation (∆????°????????????, ∆????°௔ௗ௦), were determined, and the results were analyzed in relation to the formation of nanosized aggregates. The results showed that saponins are strong surfactants and form stable nanomicelles even at low concentrations
Keywords: saponin; surfactant; micelle